Cleft lip and palate and related factors: A 10 years study in university hospitalised patients at Mashhad - Iran - Morteza Noorollahian; Mohsen Nematy; Atiyeh Dolatian; Hengameh Ghesmati; Saeed Akhlaghi; Gholam Reza Khademi (Wolters Kluwer Medknow Publications, 2015)
Background: Oral-facial clefts including cleft lip and palate are the most common congenital malformations of the head and neck. Environmental factors such as maternal hormonal disorders, use of psychiatric medications, vitamin and folic acid deficiency, hypoxia, cigarette smoking and maternal obesity and overweight can affect the incidence of these disorders. In Iran, one of the associated problems is a lack of accurate statistics regarding the present status of the patients, which can cause a disturbance in the health programmes of Ministry of Health and Medical Education. The aim of this study was to report the status of 398 cases of cleft lip and palate in Sheikh and Imam Reza Hospitals of Mashhad over a 10-year period. Materials and Methods: This retrospective descriptive study was performed using data collection method and included the evaluation of the recorded files and completing the data forms. In this study, the file records of 398 patients referring to Mashhad Sheikh and Imam Reza (P.U.H) Hospitals were studied, from the beginning of 2002 to the end of 2011; the obtained data from the files were collected and classified. Results: The highest frequency was related to cleft palate alone (40.7%); frequencies were lower regarding the cleft lip and palate and cleft lip alone (34.41% and 24.87%, respectively). Approximately, half of the patients were from rural areas of the city and had articulation disorders. Most of the patients were the first-born children of the family and their parents were consanguineously married; about one-third of the patients had a family history of the disease. Conclusion: According to the results of the present study, cleft lip is more frequent in males and cleft palate is more prevalent in females; the obtained results are consistent with the global statistics.